2018
DOI: 10.1016/j.jamda.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antipsychotic Prescribing Behaviors for Nursing Home Residents With Dementia: A Qualitative Study

Abstract: Implementing evidence-based antipsychotic prescribing practices for nursing home residents with dementia remains a significant challenge. Greater policy and institutional support is required to help stakeholders strike that "fine balance" and ultimately make better prescribing decisions. This study has generated a deeper understanding of this complex issue and will inform the development of an evidence-based intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 40 publications
0
66
0
Order By: Relevance
“…It was difficult to determine how the 'Intentions' and 'Optimism' domains influenced GPs' and community pharmacists' behaviour; these domains were also amongst the least frequently discussed by interview participants. Other studies exploring prescribing for older people have also found these domains to not be relevant [47,48]. In selecting key domains, we noted that some of the barriers and facilitators reported by HCPs impacted on a number of different domains.…”
Section: Self-monitoring Of Behaviour Memory Attention and Decision mentioning
confidence: 87%
“…It was difficult to determine how the 'Intentions' and 'Optimism' domains influenced GPs' and community pharmacists' behaviour; these domains were also amongst the least frequently discussed by interview participants. Other studies exploring prescribing for older people have also found these domains to not be relevant [47,48]. In selecting key domains, we noted that some of the barriers and facilitators reported by HCPs impacted on a number of different domains.…”
Section: Self-monitoring Of Behaviour Memory Attention and Decision mentioning
confidence: 87%
“…In this study, ‘increased staffing levels’ was the number one recommendation of participating GPs when asked what would help to reduce the prescribing of psychotropic medications in dementia. Previous studies have identified that chronic understaffing in nursing homes can hinder the nursing staff’s ability to implement non-pharmacological strategies [ 32 ] and, thus, increase pressure on GPs to prescribe sedative psychotropic medications [ 26 , 29 ]. It is likely that the prescribing pressure the GP feels from the nursing staff is a combination of all these factors; the experience level of the GP, the relationship between the nurse and the GP, and the resource constraints of the nursing home [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Personal autonomy of the resident needs to be respected, however the safety of the resident and others needs to be considered, and this can be challenging in the context of BPSD 22 . The nursing home regulator in Ireland, the Health Information and Quality Authority (HIQA) mandates the reporting of chemical and physical restraint usage in nursing homes 30 , though this presents its own challenges as reporting guidance is considered to be non-specific 22 , and any instance of restraint usage is self-reported by the nursing home 22 . There has been a recent impetus for change in the system, with the launch of the Irish National Dementia Strategy in 2014 which identified inappropriate antipsychotic prescribing as a priority for action 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The intervention is primarily targeted at nurses and GPs who provide care to nursing home residents with dementia. This is based on our previous qualitative findings which found that these two key stakeholder groups are the most central to the decision to request or prescribe an antipsychotic to a resident with dementia 21 , 22 . While the main target within the nursing home setting were nurses given their role in medication management, we considered that involving others that work in nursing homes (such as healthcare assistants) may be an important way of restructuring the social environment and promoting behaviour change 19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation